Penerapan Prinsip Education for Sustainable Development di PP Al-Qadir Yogyakarta Dalam Mempersiapkan Pesantren Enterpreneur - Muhammad Mahen; Nurochim Nurochim; sita Ratnaningsih; Wahyu Sudrajad Wahyu Sudrajad (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2023)
Islamic boarding schools are Islamic educational institutions that are ready to create a competitive and sustainable generation. The teaching of Islamic boarding schools and sustainable development have similarities in values and principles. With this, Islamic boarding schools can certainly integrate religious and general knowledge to prepare a generation that is intellectually and spiritually intelligent. In reality, the principles of sustainable development are in accordance with Islamic teachings taught at the Al-Qadir Islamic Boarding School. Therefore, Al-Qadir Islamic boarding School indirectly has an active role in supporting and realizing the principles of sustainable development. The research uses qualitative methods to answer the questions as accurately as possible. Then it is analyzed using contructivism to see how Islamic teachings can be implemented in accordance with the principles of sustainable development. Al-Qadir Yogyakarta Islamic Boarding School has role in implementing the principles of sustainable development through education. In this case researchers discovered the role of the Al-Qadir Yogyakarta Islamic Boarding School in Supporting and realizing sustainable development. KH. Masrur Ahmad MZ as an Islamic boarding school caretaker has an important role in providing understanding to teachers and students to be able to implement Islamic teachings in accordance with the principles of sustainable development education, implementation of sustainable development at Al-Qadir Islamic Boarding School.Â Keywords: sustainable development education, Implementation of sustainable development at Al-Qadir Islamic Boarding School.